Editorial – Big data through the power lens: Marker for regulating innovation - Lena Ulbricht; Maximilian von Grafenstein (Internet Policy Review, 2016)
Facing general conceptions of the power effects of big data, this thematic edition is interested in studies that scrutinise big data and power in concrete fields of application. It brings together scholars from different disciplines who analyse the fields agriculture, education, border control and consumer policy. As will be made explicit in the following, each of the articles tells us something about firstly, what big data is and how it relates to power. They secondly also shed light on how we should shape “the big data society” and what research questions need to be answered to be able to do so.
Additional information: This article is the editorial for the special issue "Big data: big power shifts?", edited by Lena Ulbricht (WZB Berlin Social Science Center, Germany) and Maximilian von Grafenstein (Humboldt Institute for Internet and Society, Germany).
Keywords: 330; Big data; Power; Regulation of innovation; Big data education; Border control; Consumer protection; Agriculture